2011
DOI: 10.1017/s0021859610001279
|View full text |Cite
|
Sign up to set email alerts
|

The role of urban agriculture in building resilient cities in developing countries

Abstract: SUMMARYThe current paper briefly summarizes the available evidence regarding the potential of urban agriculture to respond to a number of key urban challenges and reviews the perspectives on urban agriculture applied by local and national authorities. The last section of the paper briefly presents the authors’ views on the development of urban agriculture as an integral part of sustainable city development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(137 citation statements)
references
References 13 publications
1
125
0
11
Order By: Relevance
“…In some ways, such ecosystems are an ideal place to test and experiment with much needed adaptive capacity in areas vulnerable to climate change (Heffernan, 2012). The services of UA we estimated simultaneously address needs to mitigate temperature, flood, energy and food security vulnerabilities (de Zeeuw et al, 2011). Although potential agricultural returns from UA are modest, the food and revenues generated from UA could mean the difference between survival and famine (Zezza & Tasciotti, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some ways, such ecosystems are an ideal place to test and experiment with much needed adaptive capacity in areas vulnerable to climate change (Heffernan, 2012). The services of UA we estimated simultaneously address needs to mitigate temperature, flood, energy and food security vulnerabilities (de Zeeuw et al, 2011). Although potential agricultural returns from UA are modest, the food and revenues generated from UA could mean the difference between survival and famine (Zezza & Tasciotti, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…UA offers potential to ameliorate a host of urban environmental problems by increasing vegetation cover and therefore contributing to a decrease in the urban heat island (UHI) intensity (Susca et al, 2011), improving the livability of cities (Frumkin, 2003;Turner et al, 2004) and providing enhanced food security to over half of Earth's population (de Bon et al, 2009;Pearson et al, 2010). UA is connected to multiple metabolic pathways in the urban ecosystem including food provisioning (Zezza & Tasciotti, 2010), regulation of local microclimate and hydrology (Oberndorfer et al, 2007), consumption of nutrient rich "waste" water and biosolids/organic matter (Armstrong, 2009;de Zeeuw et al, 2011;Smit & Nasr, 1992), and fixation of atmospheric nitrogen (Herridge et al, 2008) and carbon (Beniston & Lal, 2012). For pollinators and other wildlife, habitat is created in the city (Goddard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lack of technologies such as a distribution cold chain or refrigerators at home reinforces the necessity to produce perishables close to urban centres. UA and PUA are discussed and promoted as strategies for sustainable development (Smit and Nasr 1992;FAO 2007;De Bon et al 2010) and often regarded as one entity, regularly labelled UPA, the abbreviation for 'urban and peri-urban agriculture' (FAO 2007;De Zeeuw et al 2011). Production in UA as well as in PUA in the Global South is characterised by the following features: It is both subsistence and market oriented, farmers and gardeners do not necessarily have a farming background (Dubbeling et al 2010), production often takes place in polluted environments (De Bon et al 2010), health risks prevail due to poor management and environmental pollution (Bryld 2003;Hamilton et al 2014), it often lacks a legal status (Bryld 2003), and leisure or recreational activities are rarely to be found (Cabannes 2006).…”
Section: Focussing On the Global Northmentioning
confidence: 99%
“…These studies showed that stakeholders associate potential benefits with urban agriculture but also detect numerous risks and uncertainties. A report by de Wilt and Dobbelaar (2005) clearly illustrates how a planned "Agropark" project in the Netherlands failed due to public averseness and active resistance from residents and the media.…”
Section: Introductionmentioning
confidence: 99%